Muslim education in the 21st century : Asian perspectives - Buang, Saeda; Chew, Phyllis Ghim Lian. (New York : Routledge, Taylor & Francis Group, 2014)
'While this book invites readers to reinvestigate the current state of affairs in Muslim education in Asia, it also pays special attention to Muslim schools perception of educational changes and reasons for such changes. Another important question that this book hopes to highlight is: Has the Muslim school been reinventing itself in the field of pedagogy and curriculum to meet the challenges of the 21st century education? Muslim schools here refer to schools whose curriculum content carry mostly religious subjects and Islam as its school culture. Typologically, it includes state-owned or privately-run madrasah or dayah in Aceh, Indonesia; pondok, traditional Muslim schools largely prevalent in the East Malaysian states and Indonesia; pesantren, Muslim boarding schools commonly found in Indonesia; imam-khatip schools in Turkey, and other variations in Asia'--
'Muslim Education in the 21st Century reinvestigates the current state of affairs in Muslim education in Asia whilst at the same time paying special attention to Muslim schools' perception of educational changes and the reasons for such changes. It highlights and explores the important question of whether the Muslim school been reinventing itself in the field of pedagogy and curriculum to meet the challenges of the 21st century education? It interrogates the schools whose curriculum content carry mostly the subject of religion and Islam as its school culture. Typologically, this include state-owned or privately-run madrasah or dayah in Aceh, Indonesia; pondok, traditional Muslim schools largely prevalent in the East Malaysian states and Indonesia; pesantren, Muslim boarding schools commonly found in Indonesia; imam-khatip schools in Turkey, and other variations in Asia. Using a host of international experts, Muslim Education in the 21st Century focuses on how Muslim educators strive to deal with the educational contingencies of their times and on Muslim schools' perception of educational changes and reasons for such changes. It will be of great interest to anyone working in higher education and particularly for anyone interested in Asian and Muslim education'--
Keywords: Educational change -- Asia; Comparative education; Islamic education -- Asia